Forest regeneration under standards of pedunculate oak (Quercus robur L.) - Jiří Libus (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2009)
Work objective was to establish reasons to the impaired vitality of woody and herbaceous vegetation growing under standards of pedunculate oak (Quercus robur L.). The paper analyzes the influence of insolation, root competition, soil moisture content and chemical composition of soil on the growth of pedunculate oak seedlings under standards. The analyses included three standards of pedunculate oak aged over 150 years, growing at an altitude of 160 m a.s.l. Controls were plots occurring at a distance of 20 m from the standards. Conclusions following out from the analyses are as follows: The number of seedlings emerged under the standards was lower than the number of seedlings emerged in the open area. Shoot height as well as root collar diameter of seedlings under the standards were lower than in the control seedlings. Total cover of herbaceous layer and height of herbs under the standards were lower than in the open area. The impaired vitality of woody and herbaceous vegetation resulted from a great amount of the fine roots of pedunculate oak standards, withdrawing water up to the wilting point. The amount of photosynthetic active radiation (PAR) under the standards was sufficient for the growth of plants.